2012
DOI: 10.1016/j.neuroscience.2012.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Transient mGlu5R inhibition enhances the survival of granule cell precursors in the neonatal cerebellum

Abstract: The generation of the most abundant neurons of the cerebellum, the granule cells, relies on a balance between clonal expansion and apoptosis during the first 10 days after birth in the external germinal layer (EGL). The amino acid glutamate controls such critical phases of cell development in other systems through specific receptors such as metabotropic glutamate receptor 5 (mGlu5R). However, the function of mGlu5Rs on the proliferation and survival of granule cell precursors (GCPs) remains elusive. We found m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In C57BL mice at 9 days only few cells (<10 per 2 mm length of EGZ and <5 per 2 mm of granular layer) were TUNEL labeled (Wullner et al, 1995 ). A more recent study reported ~55000 TUNEL positive cells per mm 3 of EGZ in 9 day mouse cerebellum (Kubera et al, 2012 ). Where TUNEL positive cells in the mouse cerebellum have been counted, the proportion is typically low; e.g., <0.5% at 10 days in the EGZ (McNamee et al, 2002 ).…”
Section: Apoptosis Autophagy and Unfolded Protein Responsementioning
confidence: 96%
“…In C57BL mice at 9 days only few cells (<10 per 2 mm length of EGZ and <5 per 2 mm of granular layer) were TUNEL labeled (Wullner et al, 1995 ). A more recent study reported ~55000 TUNEL positive cells per mm 3 of EGZ in 9 day mouse cerebellum (Kubera et al, 2012 ). Where TUNEL positive cells in the mouse cerebellum have been counted, the proportion is typically low; e.g., <0.5% at 10 days in the EGZ (McNamee et al, 2002 ).…”
Section: Apoptosis Autophagy and Unfolded Protein Responsementioning
confidence: 96%
“…In an early study comparing the development of the P0-P9 cerebellum in normal and weaver mice, mitotic figures and pyknotic cells in the EGL were always very few in normal animals (2% and less than 0.5%, respectively), mainly located in the pre-migratory half of the EGL and, in Weaver , were quickly cleared from tissue in four-seven hours [33]. Later, using the TUNEL method and/or after direct TEM observation, several reports have been published that converged to demonstrate the presence of variable amounts of apoptotic CGCs in the P0–10 EGL of normal mice [11,69] and mutants such as Lurcher [70], Reeler [3,71], and Weaver [70]. However, few investigations were devoted to analyzing the relationship of CGC proliferation and NOND in this species.…”
Section: Caspase-3 In Cerebellar Developmentmentioning
confidence: 99%
“…One therapeutic area that has not been explored at length in patients is depression. This is somewhat surprising in light of the preclinical data supporting the notion that mGlu5 antagonists may correct behaviors associated with depression and that modulation of mGlu5 receptors may promote synaptic growth and plasticity (Kubera et al, 2012;Piers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%